Environmental exposures and depression: biological mechanisms and epidemiological evidence - Bosch, Matilda van den; Meyer-Lindenberg, Andreas (Annual review of public health, 2019)
Mental health and well-being are consistently influenced-directly or indirectly-by multiple environmental exposures. In this review, we have attempted to address some of the most common exposures of the biophysical environment, with a goal of demonstrating how those factors interact with central structures and functions of the brain and thus influence the neurobiology of depression. We emphasize biochemical mechanisms, observational evidence, and areas for future research. Finally, we include aspects of contextual environments-city living, nature, natural disasters, and climate change-and call for improved integration of environmental issues in public health science, policies, and activities. This integration is necessary for reducing the global pandemic of depression.
Gesehen am 17.06.2019